Índice de qualidade da gestão pública municipal: uma proposta de mensuração - Albuquerque, Rafael Menezes (2015)
This dissertation was carried out in order to develop a quality municipal public management index (QMPMI) as a basis for decision-making by public managers, and guidance to regulatory agencies in setting priorities for inspection activities. For the study, data were collected from sites of Instituto de Pesquisa Econômica e aplicada (Ipea), da Secretaria do Tesouro Nacional (STN) e do Instituto de Pesquisa e Estratégia Econômica do Ceará (IPECE), on which was applied a multivariate data technique analysis, called factor analysis. This technique helped to reduce the number of variables and defined the weights of each set in the index. The proposed index includes indicators in the areas of health, education, employment and public finances, and that education was the area with the greater impact in the index. At the end, the QMPMI was calculated for the municipalities in Ceará in the period 2009 to 2012. The results allowed the comparison between Ceará municipalities and can be used to identify the municipalities that need more attention from regulatory agencies and that can be used as a model for other municipalities.